BRAND EQUITY, CUSTOMER SATISFACTION, DAN PURCHASE INTENTION: ANALISIS PADA FRANCHISE F&B ASING - Angela Angela; Erilia Kesumahati (Jurnal Bisnis dan Akuntansi, 2023)
The research in this article examines the factors that influence Purchase Intention in foreign F&B franchises using Service Quality and Digital Marketing variables mediated by Customer Satisfaction and Brand Equity. The study uses primary data collected through distributing questionnaires in the form of a Google Form to urban residents who have visited foreign F&B franchises in Batam City, which is then analyzed with secondary data. A total of 326 data from respondents who met the criteria were used and analyzed using the SmartPLS program. The results of the study show that Service Quality, Customer Satisfaction, Brand Equity, and Digital Marketing have a significant positive effect on Purchase Intention. This research shows that the importance of Service Quality, Customer Satisfaction, Brand Equity, and Digital Marketing in increasing Purchase Intention of F&B Franchise in Batam City.